2018
DOI: 10.1039/c8cp03696a
|View full text |Cite
|
Sign up to set email alerts
|

Doping effect of transition metals (Zr, Mn, Ti and Ni) on well-shaped CuO/CeO2(rods): nano/micro structure and catalytic performance for selective oxidation of CO in excess H2

Abstract: Investigation of how transition metal dopants regulate the microstructure of CuO/CeO2 nanorods, using XRD Reitveld refinements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The samples in Figure b had narrower FWHM (peak width at half-height) than the samples in Figure a, illustrating a better CeO 2 crystallinity. According to some literature studies, this was attributed to the weak lattice distortion of the supported Ce2 caused by a smaller Ce 3+ amount. What is more, in Figure b, the obvious CuO peak at 35.5 and 38.6° could be observed in the catalysts from Cu7.5Ce2 to Cu20Ce2, indicating that CuO aggregated and formed the bulk crystal structure. However, in Figure a, there were no peaks at 35.5 and 38.6° from Cu7.5Ce1 to Cu20Ce1, indicating that CuO was highly dispersed and formed a structure different from bulk CuO.…”
Section: Results and Discussionmentioning
confidence: 74%
“…The samples in Figure b had narrower FWHM (peak width at half-height) than the samples in Figure a, illustrating a better CeO 2 crystallinity. According to some literature studies, this was attributed to the weak lattice distortion of the supported Ce2 caused by a smaller Ce 3+ amount. What is more, in Figure b, the obvious CuO peak at 35.5 and 38.6° could be observed in the catalysts from Cu7.5Ce2 to Cu20Ce2, indicating that CuO aggregated and formed the bulk crystal structure. However, in Figure a, there were no peaks at 35.5 and 38.6° from Cu7.5Ce1 to Cu20Ce1, indicating that CuO was highly dispersed and formed a structure different from bulk CuO.…”
Section: Results and Discussionmentioning
confidence: 74%
“…Therefore, during 0–5 s mainly the surface oxygen of Cu x Ce 1– x O 2 reacted with CO to generate CO 2 , and then gaseous O 2 was adsorbed and supplemented the consumed surface oxygen, while during 5–10 s it was the lattice oxygen of Cu x Ce 1– x O 2 migrating to the surface that supplemented the consumed surface oxygen. Thus, the CO 2 formation in 0–10 s (peak α) could reflect the oxygen storage capacity and oxygen mobility of the catalysts. , In addition, since gaseous CO was almost consumed during 10–15 s of each cycle (but not completely), in 15–20 s most of the CO 2 was generated by the reaction of gaseous oxygen with carbon-containing species adsorbed on the surface of the catalysts.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On one hand, the morphology effect of ceria support was extensively investigated, since the physicochemical properties of catalysts were strongly dependent on the exposed lattice planes. It was reported that the exposure of less stable {100} and {110} facets promoted the formation of surface oxygen vacancies, while the {111} surface was favorable to transform CuO x species into monovalent copper, which enhanced the catalytic activity. , Moreover, rod-like CeO 2 was recognized to exhibit superior catalytic performance due to its specific exposed facets as well as the improved oxygen storage, reducibility, and Cu–Ce interaction. In our previous work, CeO 2 nanorod growing along [110] direction with a hexangular cross section exposing two {100} planes and four {111} planes was synthesized, and its nano/microstructure, the role of interfacial Cu–Ce interaction, and the effect of copper coverage and transition metal doping were fully illustrated. Nevertheless, the Cu–Ce interfaces in the prepared rod-like CuO–CeO 2 catalysts were limited since the synthesis of CeO 2 nanorod and the loading of copper proceeded separately; otherwise Cu­(OH) 2 was easily dissolved to form [Cu­(OH) 4 ] 2– under the strong caustic hydrothermal condition demanded for the growth of CeO 2 nanorod. In the present work, in order to promote the structural uniformity and create more Cu–Ce interfaces, a one-pot co-precipitation method at ambient temperature was designed for the synthesis of composite Cu x Ce 1– x O 2 nanorod catalysts using Cu + as copper source to avoid copper species dissolving.…”
Section: Introductionmentioning
confidence: 99%
“…For this, an excellent dispersion of Cu in the CeMgAlO matrix was observed favoring a strong synergistic effect between Cu and Ce and, hence, an enhanced catalytic activity. Thus, taking into consideration previously reported results [22][23][24][25][26] showing an enhanced synergy effect between Cu and Ce in the presence of transition-metal cations M, such as Mn [22,24], Co [25], Ni [25], and Fe [26], the present work aimed to improve the catalytic performance of this LDH-derived CuCeMgAlO mixed oxide by promoting it with 3 at.% M, with M = Mn, Fe, Co, and Ni. For the best promoted catalyst in this series, the effect of the transition metal M content in the range from 1 to 9 at.% on the catalytic performance was also investigated.…”
Section: Introductionmentioning
confidence: 99%